The Health and Economic Burdens of Lymphatic Filariasis Prior to Mass Drug Administration Programs. (25th July 2019) - Mathew, Christopher G; Bettis, Alison A; Chu, Brian K; English, Mike; Ottesen, Eric A; Bradley, Mark H; Turner, Hugo C
Abstract: Background: The Global Programme to Eliminate Lymphatic Filariasis (GPELF) was launched in 2000 with the goal of eliminating lymphatic filariasis (LF) as a public health problem by 2020. Despite considerable progress, the current prevalence is around 60% of the 2000 figure, with the deadline looming a year away. Consequently, there is a continued need for investment in both the mass drug administration (MDA) and morbidity management programs, and this paper aims to demonstrate that need by estimating the health and economic burdens of LF prior to MDA programs starting in GPELF areas. Methods: A previously developed model was used to estimate the numbers of individuals infected and individuals with symptomatic disease, along with the attributable number of disability-adjusted life years (DALYs). The economic burden was calculated by quantifying the costs incurred by the health-care system in managing clinical cases, the patients' out-of-pocket costs, and their productivity costs. Results: Prior to the MDA program, approximately 129 million people were infected with LF, of which 43 million had clinical disease, corresponding to a DALY burden of 5.25 million. The average annual economic burden per chronic case was US 115, the majority of which resulted from productivity costs. The total economic burden of LF was estimated at US 5.8 billion annually. Conclusions: These results demonstrate the magnitude of the LF burden and highlight the continued need to support the GPELF. Patients with clinical disease bore the majority of the economic burden, but will not benefit much from the current MDA program, which is aimed at reducing transmission. This assessment further highlights the need to scale up morbidity management programs. Abstract : Prior to mass drug administration, we estimate that lymphatic filariasis (LF) cost 5.25 million disability-adjusted life years and US 5.765 billion annually. The high burden of LF without control demonstrates the need for the Global Programme to Eliminate LF.